Semiquantitative analysis of genetically modified maize and soybean in food - Cazzola, María Laura (2006)
The aim of this study was to analyze quantitatively the presence of genetically modified organism in food with different composition and degree of processing. Total DNA was extracted by Dellaporta's method and GMO analysis was performed using two consecutives PCR reactions with specie specific primers (IVR and LE), screening primers (35S) and transgen specific primers (CRY and EPSPS). The quantification within the sensitivity establish by the EU was possible only in some foods (ice-cream, flours, soybean isolates and concentrates, starch). Samples with high lipid content or subjected to intense thermal treatments (such as some snacks, mayonnaise, creamy soup) could not be amplified mainly due to the presence of PCR inhibitors. Therefore the method was adequate for identification of food as GM, within the limits establish by EU, only for some Argentinean commercial food products. These findings showed that the develop method was satisfactory only for simple food that were not subject to intense thermal treatments and that do not have high lipid content and that the main limitation of the method is DNA purity.